The Development of Textbook Learning Media Based on Local Wisdom of North Sumatera - Uyuni Widiastuti; Adina S Sembiring; Mukhlis Mukhlis; Lamhot B Sihombing; Theodora Sinaga; Purbatua Manurung (BIRCU, 2020)
The textbook developed in this study is adapted to the 2013 curriculum applicable in SMA, namely the material in class X. The material is adapted to the local wisdom of North Sumatra, especially in traditional Karo songs and music. This textbook describes the traditional Karo music in the form of a kulcapi drum ensemble whose instruments consist of kulcapi, keteng-keteng and bowl. This textbook is equipped with techniques in playing the kulcapi drum on the song Piso Surit and Terang Bulan. The existence of this textbook is very helpful for Cultural Arts teachers in teaching music based on local wisdom of North Sumatera.